The Chairman of the University Board of Directors visited UMPSA Gambang Campus and its subsidiary, UMP Holdings - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
GAMBANG, 23 November 2023 - Chairman of the Board of Directors of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Dato' Seri Abdul Razak Jaafar visited UMPSA Gambang campus after his maiden visit to Pekan on November 2nd.